EFEKTIVITAS GUIDED DISCOVERY LEARNING BERBANTUAN TRANSGEO BOARD TERHADAP HASIL BELAJAR MATERI TRANSFORMASI GEOMETRI - Chandra Umbu Keba Andunara; Iona Lisa Ndakularak; Darius Imanuel Wadu (Jurnal Ilmiah Matematika Realistik, 2026)
This study aimed to examine the effectiveness of the Guided Discovery Learning model supported by the TransGeo Board in enhancing students’ mathematics learning outcomes, particularly in the topic of geometric transformations. A quantitative approach was employed using a quasi-experimental pretest–posttest control group design to compare students’ achievement before and after the intervention. The participants were Grade IX students of SMP Katolik Andaluri, divided into an experimental group and a control group, each consisting of 28 students. Data were collected through pretests and posttests and analyzed using descriptive and inferential statistics with the aid of SPSS software. The novelty of this research lies in the integration of Guided Discovery Learning with the TransGeo Board as a visual and manipulative learning tool that facilitates students’ discovery of geometric transformation concepts. The results showed that the experimental group achieved a higher average posttest score than the control group, with the difference found to be statistically significant. In addition, the N-Gain analysis indicated that the improvement in learning outcomes among students in the experimental group was categorized as high. These findings demonstrate that the implementation of Guided Discovery Learning assisted by the TransGeo Board is effective in improving students’ understanding of concepts and overall achievement in learning geometric transformations.